Extracellular vesicle: A magic lamp to treat skin aging, refractory wound, and pigmented dermatosis? - Wu, Haiyan; Zhang, Zhenchun; Zhang, Yuemeng; Zhao, Zhenlin; Zhu, Hongming; Yue, Changwu (Frontiers in Bioengineering and Biotechnology, 2022)
Exposure of the skin to an external stimulus may lead to a series of irreversible dysfunctions, such as skin aging, refractory wounds, and pigmented dermatosis. Nowadays, many cutaneous treatments have failed to strike a balance between cosmetic needs and medical recovery. Extracellular vesicles (EVs) are one of the most promising therapeutic tools. EVs are cell-derived nanoparticles that can carry a variety of cargoes, such as nucleic acids, lipids, and proteins. They also have the ability to communicate with neighboring or distant cells. A growing body of evidence suggests that EVs play a significant role in skin repair. We summarize the current findings of EV therapy in skin aging, refractory wound, and pigmented dermatosis and also describe the novel engineering strategies for optimizing EV function and therapeutic outcomes.